Women's Leadership Communication Style in Public Policy Implementation - Niananda, Vani; Nurdiarti, Rosalia Prismarini; Mutiara, Mutiara (Jurnal Ekonomi dan Bisnis Digital, 2024)
Good leadership requires the ability to communicate with all elements related to being led so that all organizational goals can be achieved. The presence of women in various public sectors shows the suitability of women to take part and even hold policy-making positions. The presence of several female leaders in Indonesia who occupy leadership positions and the presence of the first female Deputy Regent of Wakatobi elected to lead the Wakatobi Regency area needs to be used as a bullet in the progress of opening up opportunities for women to move in the public space. The focus of this research objective is on what kind of communication style is applied to the female leadership of the Deputy Regent of Wakatobi when leading Wakatobi district in implementing public policy. The research uses a qualitative descriptive approach with a case study method. Data collection techniques were carried out using observation, in-depth interviews and documentation. The 6 informants were selected using purposive sampling technique. The research results show that the communication style of women's leadership in implementing existing public policies is two-way communication; structured; open to receiving suggestions; fast handling.